The Use of Urinary Biomarkers to Assess Exposures to Polycyclic Aromatic Hydrocarbons (PAHs) and Other Organic Mutagens - Keir, Jennifer Leslie Ann (Université d'Ottawa / University of Ottawa, 2017)
Exposure to combustion emissions poses a threat to human health due to the complex mixture of toxic compounds. Polycyclic aromatic hydrocarbons (PAHs) are one group of compounds found within this mixture, and have known carcinogenic and mutagenic properties. Rates of exposure to PAHs depend on a wide range of variables including, but not limited to, demographic, geographical location, dietary habits, smoking habits, and occupation. Understanding magnitude of exposure to these compounds in various groups is imperative to highlight at-risk populations and provide appropriate exposure reduction recommendations. Here, urinary biomarkers are used as a non-invasive, convenient way to assess an individual’s exposure to combustion emissions. Urinary measurements of metabolites of individual PAHs as well as compounds indicative of a physiological condition resulting from combustion emission exposure are used to infer exposure. Pairing urinary data with information from questionnaires collecting data on possible sources of combustion by-product exposure was used to determine situations of high exposures. This thesis investigated the influence of demographic, lifestyle, and occupational factors on urinary levels of PAH metabolites and/or urinary mutagenicity. More specifically, statistical methods were used to analyze population data compiled for the Canadian Health Measures Survey (CHMS). Smoking, age, and sex were identified as the variables most predictive of urinary PAH metabolite concentrations in Canadians. Together with the other demographic and lifestyle variables examined, 24-50% of the variation in the various PAH metabolites was explained. Furthermore, the results obtained illustrated that utilizing PAH metabolites other than the traditionally used 1-hydroxypyrene may be more suitable for certain exposure scenarios (e.g., fluorene metabolites for tobacco smoke exposure). Occupational exposures to combustion emission were investigated in firefighters as they experience above average risk of cancer, thus paired with their obvious involvement with combustion, are an ideal population to apply the use of urinary biomarkers to assess PAH and combustion exposure. The effect of participating in fire suppression activities (i.e., firefighting) on urinary levels of selected PAH metabolites and organic mutagens was examined. Levels of external PAH exposures were assessed using personal air monitoring and surface wipes of skin. Significant increases in urinary PAH metabolites and mutagenicity were seen after fire suppression events. Empirical relationships between urinary PAH metabolites and duration of fire event and skin concentrations of PAHs suggested that dermal contamination during live fire events is a major route of exposure. Overall, the results from both studies identified factors that may affect an individual’s concentrations of urinary biomarkers of combustion emission exposure. This may be used to identify at-risk populations and/or determine effective exposure reduction techniques to these hazardous compounds.
Keywords: Urinary biomarkers; Polycyclic aromatic hydrocarbons; Organic mutagens; Combustion; Firefighters